ANALISIS PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR TERHADAP HARGA SAHAM PADA SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Laoh, Saartje Dompas (JBE (Journal of Business and Economics); Volume 12 No.1, 2013 JBE UNKLAB, 2013)
This research aims to find out the significant of inflation, interest rate and exchange rate toward stock price of banks listed in Bursa Efek Indonesia in 2009-2012. The sample is chosen by using purposive sampling technique. To analyze the data, multiple linear regression method is used. The results show that, partially, inflation and exchange rate insignificantly affect stock price, while interest rate negatively significantly affect stock price. Simultaneously, inflation, interest rate and exchange rate significantly affect stock price.